The treatment and prognosis of pediatric adrenocortical carcinoma - Yu Lin; Kairui Zhai; Zhiyun Zhu; Jianyu Han; Shen Yang; Paul D. Losty; Hong Qin (Holistic Integrative Oncology)
Abstract This review comprehensively assesses the treatment modalities and prognostic outcomes of pediatric adrenocortical carcinoma (ACC), a rare malignancy with significant clinical challenges. Through a systematic literature search of PubMed using the term "childhood adrenocortical carcinoma," supplemented by EndNote-assisted duplicate removal and manual verification, we synthesize current evidence on the clinical characteristics, staging criteria, pathological diagnosis, and imaging features of this disease. The analysis highlights that surgical resection remains the cornerstone of treatment, particularly for stage I/II patients who may achieve long-term survival without recurrence. However, prognosis deteriorates markedly in advanced stages, with stage IV patients exhibiting distant metastases facing poor outcomes. Adjuvant therapies such as postoperative chemotherapy and mitotane are critical to improving survival, yet further research is needed to optimize therapeutic strategies. These findings aim to guide clinicians in tailoring diagnostic and management approaches for pediatric ACC.